Mobile health applications for atrial fibrillation: A readability and quality assessment. (15th October 2019) - Ayyaswami, Varun; Padmanabhan, Divya L.; Crihalmeanu, Tudor; Thelmo, Franklin; Prabhu, Arpan V.; Magnani, Jared W.
Abstract: Background: Mobile health applications may improve patient education and self-care for a complex condition such as atrial fibrillation (AF). Little is known about the accessibility of mobile health applications ("apps") and their readability. We evaluated the readability and quality of available apps for AF. Methods: We searched the Apple and Google Play app stores with the terms "atrial fibrillation" and "afib." We downloaded English-language apps (up to n = 100 for each term) and categorized them by name, App store, cost, content, uploading agency (heath care associated [HCA] versus non-HCA), target audience (health care professional [HCP] versus non-HCP), scientific validity (i.e., citation of peer-reviewed or validated medical information), and user ratings. We analyzed the text of apps intended for a non-HCP target audience for readability with 10 established measures. Results: Of the 206 downloaded apps, 50.5% were excluded as unrelated to AF, inaccessible, or non-English language. The majority of apps contained information about AF (63.2% Apple, 52.2% Google Play) and AF detection (52.6% Apple, 56.5% Google Play). A minority of non-HCP apps contained scientifically validated content (Apple, 15.8%; Google Play, 13.0%; P = NS). App mean readability was grade 12.1 ± 2.6. Conclusions: Most AF apps lacked scientific validation and were written at excessively high reading-grade levels. Our results suggest caution with mobile health apps, particularly for users with limited health literacy. There is potential opportunity for a multi-disciplinary effort by regulatory agencies, healthcare organizations, and app stores to improve relevance, scientific validity, and readability of AF apps for patients with this complex and morbid disease. Highlights: We systematically examined smartphone apps for atrial fibrillation. In the majority of apps, we identified content that lacked scientific validation. Materials for patient education were written at very high reading-grade levels. We suggest professional society guidelines for app quality and readability.